Currency Unions, Economic Fluctuations, and Adjustment : Some New Empirical Evidence - Prasad, Eswar (IMF Working Papers; Working Paper ;, 1996)
This paper examines the sources of disturbances to output in the United States and a set of EU countries and analyzes labor market adjustment mechanisms in these two economic areas. Comparable datasets comprising 1-digit sectoral data for eight U.S. regions and eight European countries are constructed and used to compare the degree of industrial diversification and the relative importance of different sources of shocks to output growth. Both areas are found to be subject to similar overall disturbances although a disaggregated perspective reveals some important differences. The major difference, however, is in labor market adjustment. Interregional labor mobility appears to be a much more important adjustment mechanism in the United States, which has a more integrated labor market than the EU.